IMPLEMENTASI MODEL PEMBELAJARAN TEAM GEAM TOURNAMENT UNTUK MENINGKATKAN HASIL BELAJAR AGAMA HINDU SISWA KELAS V SEKOLAH DASAR - komang, Badra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the improvement of Hinduism learning outcomes through the implementation of the Team Game Tournament learning model for fifth grade students of SD Negeri 4 Pertima. The background of this study is based on the low student learning outcomes caused by the use of conventional learning methods that do not actively involve students. This study is a classroom action research carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects of this study were 30 fifth grade students of SD Negeri 4 Pertima. Data were collected through learning outcome tests and observations of student learning activities. The results of data analysis showed an increase in student learning outcomes in each cycle. In cycle I, the average student score reached 71.33 with classical completeness of 70%, and increased in cycle II to 83.67 with classical completeness reaching 93.33%. These results indicate that the TGT learning model is effective in improving students' Hinduism learning outcomes. Thus, it can be concluded that the implementation of the Team Game Tournament learning model can improve the Hinduism learning outcomes of fifth grade students of SD Negeri 4 Pertima.